THE DYNAMICS OF USING NAMES AS A SOCIO-CULTURAL PROBLEM (Scientific journal of the Fergana State University, 2024)
As the human factor lies at the core of post-linguistic researches, any unit related to humans might be a pertinent subject of investigation. People's names constitute one such dynamic language unit. This article addresses two scientific disciplines studying names as a main unit: onomastics, and anthroponymics which eventually split off from onomastics. The article also mentions other elements that are thought to be significant when deciding on a name and incorporating it into a custom.